COVID-19 infection and the kidneys: Learning the lesson. Issue 7 (July 2021) - Soliman, Neveen A.
Abstract: The novel coronavirus 2019 pandemic has become a global health crisis. In an attempt to decipher how kidneys are affected by COVID-19 infection, this review focuses on pathogenic and clinical links between COVID-19 infection and the kidneys. SARS-CoV-2 infected patients are target for kidney affection, renal tropism, among other multiorgan complications. COVID-19 related kidney affection is reported not only in infected chronic kidney disease patients but also in those with no prior history of kidney disease. As nephrologists try to keep up with the rapidly evolving, sometimes hasty, reports on renal affection in COVID-19, kidneys continue to be deleteriously affected particularly in critical care settings. This review aims to briefly portray renal involvement in COVID-19 amid this unprecedented deluge of scientific data. Based on gained knowledge and expertise, it is prudent to develop and regularly update preventive, diagnostic and therapeutic strategies to improve clinical outcome and reduce mortality.